Association between killer cell immunoglobulin-like receptor (KIR) polymorphisms and systemic lupus erythematosus (SLE) in populations: A PRISMA-compliant meta-analysis. Issue 10 (March 2017) - Liang, Hui-ling; Ma, Shu-juan; Tan, Hong-zhuan
Abstract: Background: Recently, a growing number of studies show that the killer cell immunoglobulin-like receptor (KIR) gene polymorphisms may play a role in the systemic lupus erythematosus (SLE) susceptibility. Nonetheless, the results were inconsistent. Thus, a meta-analysis was carried out by integrating multiple research to clarify the association between KIR polymorphisms and SLE susceptibility. Methods: The Web of Science, Embase (Ovid), PubMed, Elsevier Science Direct, the Chinese Biomedical Database and CNKI, Wanfang databases (last search was updated on May 15, 2016) were systematically searched to select studies on addressing the association between the KIR polymorphisms and susceptibility to SLE in populations. The odds ratio (OR) with 95% confidence interval (95% CI) was calculated. Results: A total of 10 published case-control studies involving 1450 SLE patients and 1758 controls were available for this meta-analysis. Results suggested that KIR2DL1 might be a risk factor for SLE (OR2DL1 =1.047, 95% CI=1.011–1.083) in all subjects. The KIR2DL3, KIR2DL5 were identified as protective factors for SLE in Asian populations (OR2DL3 = 0.215, 95% CI = 0.077–0.598; OR2DL5 = 0.588, 95% CI = 0.393–0.881), but not in Caucasians. Conclusions: The meta-analysis results suggested that 2DL1 might be a potential risk factor and 2DL3, 2DL5 might be protective factors for SLE in Asians but not in Caucasians.